Nilai-Nilai Moderasi Beragama dalam Syair Lagu Madura Untuk Pengembangan Pribadi Konselor Multikultural - Jannah, Syaifatul; Qibtiyah, Luthfatul; Ahmadi, Ahmadi (Proceedings of Annual Conference for Muslim Scholars, 2022)
This study aims to examine the values ​​of religious moderation contained in the Madura songs as an effort to develop the personal development of multicultural counselors. This is important so that the counselor can better appreciate the counselee's cultural differences, including religious differences. The research method used is a qualitative method with the type of Gadamerian hermeneutics, namely a method for interpreting the meaning in a text by involving the interaction between the text and the researcher. The results showed that there were six values ​​of religious moderation in the nine Madurese songs studied, namely anti-violence, national commitment, having a sense of brotherhood, reminding each other, and being sensitive.